First, R1 and R4 are in series with each other, suppose these two form an equivalent resistor R5, then,

R5 = R1+R4

Now this R5, R3 and R3 are in parellel to each other. Suppose these three form a equivalent resistor of R, then,

(1/R) = (1/R5) +(1/R2)+(1/R3)

(1/R) =...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

First, R1 and R4 are in series with each other, suppose these two form an equivalent resistor R5, then,

R5 = R1+R4

Now this R5, R3 and R3 are in parellel to each other.

Suppose these three form a equivalent resistor of R, then,

(1/R) = (1/R5) +(1/R2)+(1/R3)

(1/R) = (1/(R1+R4))+(1/R2)+(1/R3)

Multiply, Right hand side of the equation by ((R1+R4)R2R3)/((R1+R4)R2R3)

(1/R) = (R2R3+R3(R1+R4)+R2(R1+R4))/(R2R3(R1+R4))

By taking the reciprocal,

R = (R2R3(R1+R4))/(R2R3+R3(R1+R4)+R2(R1+R4))